An Experimental Analysis of Air-Steam Gasification in A Fluidized Bed - V.Chokkalingam, S.Rajendran, P.Mohanraj, S.Jeyan (Mathematical Statistician and Engineering Applications, 2023)
This study applies a self-heated Fluidized bed gasifier as the reactor and uses char as the catalyst to study the characteristics of hydrogen production from biomass gasification. Air and oxygen/steam are utilized as the gasifying agents. The maximum lower heating value of fuel gas reaches 11.11 MJ/N m3 for biomass oxygen/steam gasification. Over the ranges of operating conditions examined, the maximum hydrogen yield reaches 45.16 g H2/kg biomass. For biomass oxygen/steam gasification, the content of H2 and CO reaches 63.27–72.56%, while the content of H2 and CO gets to 52.19–63.31% for biomass air gasification. The ratio of H2/CO for biomass oxygen/steam gasification reaches 0.70–0.90, which is lower than that of biomass air gasification, 1.06–1.27. The experimental and comparison results prove that biomass oxygen/steam gasification in a Fluidized bed gasifier is an effective, relatively low energy consumption technology for hydrogen-rich gas production.